Novel Theranostic Approaches Targeting CCR4-Receptor, Current Status and Translational Prospectives: A Systematic Review - Joana Gorica; Maria Silvia De Feo; Ferdinando Corica; Marko Magdi Abdou Sidrak; Miriam Conte; Luca Filippi; Orazio Schillaci; Giuseppe De Vincentis; Viviana Frantellizzi (MDPI AG, 2023)
Background: With the high mortality rate of malignant tumors, there is a need to find novel theranostic approaches to provide an early diagnosis and targeted therapy. The chemokine receptor 4 (CCR4) is highly expressed in various tumors and plays an important role in tumor pathogenesis. This systematic review aims to provide a complete overview on clinical and preclinical applications of the CCR4 receptor as a target for theranostics, using a systematic approach to classify and assemble published studies performed on humans and animals, sorted by field of application and specific tumor. Methods: A systematic literature search of articles suiting the inclusion criteria was conducted on Pubmed, Scopus, Central, and Web of Science databases, including papers published from January 2006 to November 2022. Eligible studies had to be performed on humans and/or in vivo/in vitro studying CCR4 expression in tumors. The methodological quality was assessed through the Critical Appraisal Skills Programme (CASP) assessing only the studies performed on humans. Results: A total of 17 articles were screened. The articles were assessed for eligibility with the exclusion of 4 articles. Ultimately, 13 articles were selected for the qualitative analysis, and six articles were selected for the critical appraisal skills program. Conclusions: The development of new radionuclides and radiopharmaceuticals targeting CCR4 show promising results in the theranostics of CCR4 sensible tumors. Although to widen its use in clinical practice, further translation of preclinical to clinical data is needed.